Xianbei Zoomorphic Plaques: Art, Migration, and Human-Environment Entanglement - Fan Zhang (Arts, 2022)
This paper adopts an ecological perspective to investigate the visual and material remains associated with the Xianbei people, a nomadic group active in Northeast Asia from the turn of the common era to the early medieval period. Through the study of metal plaques bearing animal motifs and the environmental contexts of these artworks, I articulate the entangled relationship between humans, animals, and nature. More specifically, this research highlights three groups of zoomorphic designs, including the deer, the horse, and the human–animal juxtaposition. By investigating the stylistic changes and geographical distributions of these three types of zoomorphic metal plaques, I analyze the various roles that animals played in the Xianbei society and the different ways in which the Xianbei people engaged with animals. The shifting relationship between humans and animals as reflected in the zoomorphic metal plaques, I argue, likely resulted from the changing environment of the Xianbei people as they migrated from the Greater Khingan Range to the southern Mongolian Steppe and, finally, to North China. At various stages of their migration, the Xianbei people conducted different modes of living, ranging from hunting, pastoral nomadism, to a sedentary lifestyle, which significantly shaped the design of their zoomorphic metal plaques.